Study of DNA interaction and cytotoxicity activity of Oxidovanadium(V) complexes with ONO donor schiff base ligands - Sahu, G.; Tiekink, Edward R. T. *; Dinda, Rupam (MDPI, 2021)
Two new oxidovanadium(V) complexes, (HNEt3)[VVO2L] (1) and [(VVOL)2μ-O] (2), have been synthesized using a tridentate Schiff base ligand H2L [where H2L = 4-((E)-(2-hydroxy-5-nitrophenylimino)methyl)benzene-1,3-diol] and VO(acac)2 as starting metal precursor. The ligand and corresponding metal complexes are characterized by physicochemical (elemental analysis), spectroscopic (FT-IR, UV–Vis, and NMR), and spectrometric (ESI–MS) methods. X-ray crystallographic analysis indicates the anion in salt 1 features a distorted square-pyramidal geometry for the vanadium(V) center defined by imine-N, two phenoxide-O, and two oxido-O atoms. The interaction of the compounds with CT–DNA was studied through UV–Vis absorption titration and circular dichroism methods. The results indicated that complexes showed enhanced binding affinity towards DNA compared to the ligand molecule. Finally, the in vitro cytotoxicity studies of H2L, 1, and 2 were evaluated against colon cancer (HT-29) and mouse embryonic fibroblast (NIH-3T3) cell lines by MTT assay. The results demonstrated that the compounds manifested a cytotoxic potential comparable with clinically referred drugs and caused cell death by apoptosis.